PATHOGENETICALLY BASED CONSERVATIVE THERAPY IN THE COMPLEX TREATMENT OF ACUTE ADHESIVE SMALL BOWEL OBSTRUCTION - Choriev Khaitmurod Kultura ugli; Mustafakulov Ishnazar Boynazarovich; Djuraeva Zilola Aramovna (Research Focus International Scientific Journal, 2026)
Acute adhesive small bowel obstruction (ASBO) remains one of the most common causes of emergency abdominal surgery and is characterized by a high risk of complications and recurrence. Conservative treatment is effective only in some patients, and the lack of a pathogenetic approach limits its results. This study utilized a diagnostic algorithm using clinical, laboratory, and instrumental criteria. The use of a comprehensive conservative approach was associated with favorable clinical outcomes and improved motor-evacuation function, as measured by laboratory, radiographic, and ultrasound examinations. Post-treatment duplex ultrasound imaging revealed statistically significantly higher Vmax and Vmin values ​​in patients with localized adhesions compared to those with widespread adhesions (p<0.001). This pathogenetically substantiated comprehensive conservative therapy is an effective component of OSTKO treatment and can be used to increase the rate of successful non-surgical resolution of the disease and optimize the choice of subsequent treatment.